Recycling of black slag for use as raw material in the construction sector. Case study ANDEC - Alvarado Márquez, Mariana de Jesús (Revista Universidad de Guayaquil, 2019)
The present study aims to identify the importance of black slag as a raw material or component in the construction sectors, through knowledge of the profile of the sector's clients and their perception of the use of slag for this important sector of the economy. For this, a qualitative and quantitative investigation was carried out which allowed to determine the use of slag for minor works and adjustments within the company ANDEC and to undertake a social project using this non-profit product, for the repair of streets, landfills or minor construction for the community, creating a positive perception within the community about the use of slag for construction applications.
Keywords: Slag; Steel; construction